Methane-derived authigenic carbonates on accretionary ridges: Miocene case studies in the northern Apennines (Italy) compared with modern submarine counterparts. (April 2019) - Argentino, C.; Conti, S.; Crutchley, G.J.; Fioroni, C.; Fontana, D.; Johnson, J.E.
Abstract: We present new field data from three outcrops of Miocene methane-derived authigenic carbonates in the foredeep of the northern Apennines that contain chemosynthetic fauna and record a long history (∼1 Ma) of shallow fluid seepage linked to seafloor anaerobic oxidation of methane. The studied outcrops show similar features in terms of carbonate morphology, facies, spatial distribution and lateral and vertical contacts with the enclosing sediments. Methane-derived carbonates occur in two structural positions: 1) on the slope of the accretionary wedge in hemipelagites draping buried thrust-related anticlines, and 2) at the leading edge of the deformation front in the inner foredeep, within fault-related anticlines standing above the adjacent deep seafloor as intrabasinal ridges. We compare fossil seeps with two extensively investigated modern analogues: the Hikurangi Margin, offshore New Zealand and Hydrate Ridge, on the Cascadia margin, offshore the U.S.A. These analogues share a similar compressive structural setting and are marked by the presence of variably extensive and voluminous methane-derived carbonate bodies and chemosynthetic fauna on the present-day seafloor. The comparison allows us to propose a model for the evolution of fluid seeps on thrust-related ridges. At the deformation front, uplift and geometry of the anticlinal ridges are controlled by the growth of splay faults, mostly blind, connected to the basal detachment, favoring the migration of fluids toward the incipient anticline. Fold development generates extensional stresses in the hinge zone of the anticline, promoting the development of normal faults; fluid migration pathways and seafloor seeps shift from the forelimb toward the crest of the ridge as the structures evolve. In the slope setting, far from the deformation front, thrust faults and extensional faults in buried anticlines remain the main fluid migration pathways to sustain seepage at the seafloor. After reaching a mature stage within the wedge, the structure is less active and buried in the slope environment of the evolved prism. Highlights: We provide summary of recurring features at seep outcrops in the northern Apennines. Fossil seeps are compared with analogues from modern compressive settings. The onset and evolution of seeps are linked to the development of anticlinal ridges. We propose a new evolutionary model for seeps on accretionary ridges.